EVALUASI STRUKTUR EKSISTING GEDUNG GRAHA PT PETROKIMIA GRESIK - Muhammad Wahyu Firdani; Muhammad Sigit Darmawan; Budi Suswanto; Gentur Prihantono (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This paper discusses the Evaluation of the Existing Structure of the Graha Building of PT Petrokimia Gresik. The building was constructed on December 6, 2021, and handed over on June 28, 2023. However, in August 2025, cracks were discovered in the rear section of the building. These cracks were found in areas such as the staircase access from the 1st to the 2nd floor, the head office's room, and on beams across several floors. Consequently, a special identification of this damage is required, encompassing visual inspection, concrete surface hardness testing, concrete core sampling, and analysis using SAP2000. Therefore, a technical study is necessary to analyze the structural strength of the existing building. Based on the structural system analysis, the selected strengthening methods are: Adding new post columns using IWF 250 x 250 sections, Injecting the concrete cracks, Strengthening the cantilever beams using Carbon Fiber Reinforced Polymer (CFRP). Furthermore, risk mitigation for these work methods is required to ensure the project implementation can be completed safely.